PENGARUH KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KEPUASAN KERJA (STUDI PADA PELAKSANA IMUNISASI DI DINAS KESEHATAN KABUPATEN PATI ) - 11.42.02.0077, Rr. Tri Murtiningsih (Jurnal Mahasiswa Pasca Sarjana, 2013)
The optimality insufficient of immunisation employeeâs performance is warked with six puskesmas / health centre which yet has been fullfil the range target of UCI. There is still a KIPI case, the lack of optimality of employeeâs awareness in doing serving to society. Another problem toward officerâs immunisationâs performance in DKK Pati / health office of Pati regency is that there is 2 KIPI case. KIPI case is an indicator that immunisation officerâs performance in DKK Pat / health office of Pati Regency is not optimal (DKK Pati year 2012). This study has anain to know the influence of competency and compensation toward employeeâs performance with job satisfaction mediation in immunisation worker in DKK Pati. The study has been done toward 143 immunisation worker in Puskesmas Pati Regency. Sampling technique using purposive sampling and taking civil servant workers who has ever join an immunisation training about 104 person. Statistics technique which is used is validity test with matrix component, Reliability test which alfa cronbach, double regresion analysis, t test and r2 test with adjusted r square. The result of the study is known that competency has an influence toward job satisfaction. Compensation has a positive influence toward job satisfaction. Competency has a positive influence toward performance. Compensation has an influence toward performance. Job satisfaction has a positive toward the performance of immunisation worker in DKK Pati. Job satisfaction doesnât bring mediation of competency influence toward immunisation workerâs performance in DKK Pati. Job satisfaction doesnât bring mediation of compensation influence toward immunisation workerâs performance in DKK Pati. Keyword : Competency, Compensation, Job Satisfaction and Performance.